IF-dimension of Modules - Mahdou, Najib; Tamekkante, Mohammed (Communications in Mathematics and Applications, 2010)
In this paper, we introduce a dimension, called IF-dimension, for modules. With this new dimension we gives a new characterization of IFD-dimension of rings; see [4]. The relations between the IF dimension and other dimensions are discussed.